An insight into the practical budgeting for productions of production houses / Shahrul Azlan Mohd. Zulkifli - Mohd. Zulkifli, Shahrul Azlan (1990)
This project paper is done with the intention of gaining an insight into the practical aspect of budgeting applied by the management of a Production House for its productions. The study was deemed essential as there were many grouses about the film industry being not so financially lucrative. There were a number of failed financial ventures into this glamourous industry. The creative and artistic elements of this business field have been discussed many a time in various media and sometimes with a touch of nostalgia. However, only a few have touched on the financial and management aspects. Thus the author would like to gain an insight into a component of that important but least studied aspect of the business, that is budgeting and how it is practised in this highly creative and artistic business in Malaysia.